2020
DOI: 10.3389/fphar.2020.01057
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Therapeutic Effect of Ultrasound Combined With Microbubbles on Muscular Tumor Xenografts With Appropriate Acoustic Pressure

Abstract: Ultrasound combined with microbubbles (USMB) is a promising antitumor therapy because of its capability to selectively disrupt tumor perfusion. However, the antitumor effects of repeated USMB treatments have yet to be clarified. In this study, we established a VX2 muscular tumor xenograft model in rabbits, and performed USMB treatments at five different peak negative acoustic pressure levels (1.0, 2.0, 3.0, 4.0, or 5.0 MPa) to determine the appropriate acoustic pressure. To investigate whether repeated USMB tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(50 reference statements)
3
2
0
Order By: Relevance
“…In line with this study, Hwang et al observed a positive correlation between inertial cavitation (1-9 MPa PNP) and blood vascular damage in vivo [45]. This microbubble-driven blood vessel narrowing might explain the significant decrease in blood perfusion previously observed in numerous preclinical studies [46][47][48][49][50][51]. On the other hand, some studies have shown that USMB can induce blood vessel dilation and local increase in blood perfusion [50,52,53].…”
Section: The Effect Of Biological Barriers On the Pharmacokinetics Of Ocular Drug Deliverysupporting
confidence: 84%
“…In line with this study, Hwang et al observed a positive correlation between inertial cavitation (1-9 MPa PNP) and blood vascular damage in vivo [45]. This microbubble-driven blood vessel narrowing might explain the significant decrease in blood perfusion previously observed in numerous preclinical studies [46][47][48][49][50][51]. On the other hand, some studies have shown that USMB can induce blood vessel dilation and local increase in blood perfusion [50,52,53].…”
Section: The Effect Of Biological Barriers On the Pharmacokinetics Of Ocular Drug Deliverysupporting
confidence: 84%
“…In line with this study, Hwang et al observed a positive correlation between inertial cavitation (1-9 MPa P neg ) and blood vascular damage in vivo [45]. This microbubbledriven blood vessel narrowing might explain the significant decrease in blood perfusion previously observed in numerous preclinical studies [46,47,48,49,50,51]. On the other hand, some studies have shown that USMB can induce blood vessel dilation and local increase in blood perfusion [50,52,53].…”
Section: Mechanisms Underlying the Therapeutic Use Of Ul-trasound And...supporting
confidence: 86%
“…Detachment of HUVEC after exposure to USMB was previously reported at similar ultrasound pressures [37]. In conclusion, cell detachment in combination with insufficient barrier tightness [51] make HUVEC not an ideal endothelial barrier model for investigating the effect of USMB on molecular permeability. In future studies, co-culture of HUVEC with other supportive cells, such as pericytes, could improve the tightness of the barrier and provide a more suitable model for permeability studies [52,53].…”
Section: Effect Of Usmb On the Permeability Of Anti-cxcr4 Nanobody Ac...supporting
confidence: 53%
“…Additionally, greater tumor cell death and vessel damage were reported at a higher pressure of 4.0, and 5.0 MPa. They found the optimal acoustic pressure to be 4.0 MPa, at which a significant anti-tumor effect was observed, with no damage seen around the surrounding tissue [61] . Several other studies have also looked at the effect of different ultrasound pressure [62] , [63] , [64] , [65] , [66] .…”
Section: Ultrasound-stimulated Microbubbles (Usmb)mentioning
confidence: 99%
“…Several studies, primarily in vitro , have recently been conducted in investigating the effect of USMB and radiation on various tumor cell types including metastatic follicular thyroid carcinoma cells (FTC-238), non-small cell lung carcinoma cells (NCI-H727) with kV and MV energies [75] , esophageal squamous cell carcinoma cell lines (KYSE-410, KYSE-1140, KYSE-510) [60] , [61] , [87] , and ovarian cancer [88] . In these studies, a significant increase in tumor cell death was observed with the combination of USMB treatments alongside XRT compared to either modality alone.…”
Section: In Vitro Radiosensitization Effect Of Usmbmentioning
confidence: 99%